NANOCOMPOSITE SURFACES – A REVIEW - Khan, T. I. (The Nucleus, 2010)
The development of nanocomposite surfaces offers significant improvements in mechanical properties over conventional microstructured surfaces. However, to develop nanostructured surfaces for abrasive wear resistant applications still remains a challenge. This paper gives an overview of some of the more successful spraying techniques such as High Velocity Oxy-Fuel (HVOF) spraying that have been used to deposit thick nanostructured WCCo based coatings. The retention of the nanostructure developed in the feedstock powders through control of spraying parameters has some limited success in preventing decarburization of the WC nano-sized dispersion in the Co matrix. The use of a novel duplex Co-coated powder has the effect of eliminating decarburization and this is reflected in a noticeable increase in mechanical and wear resistant properties of the final coating. Cold gas dynamic spraying techniques have also been used to control the final composition and grain structure of WC-Co based coatings and the corresponding properties changes are compared and discussed.